Enhancing resistance to Salmonella typhimurium in yellow-feathered broilers: a study of a strain of Lactiplantibacillus plantarum as probiotic feed additives - Yin, Yangyan; Peng, Hao; Bai, Huili; Pei, Zhe; Chen, Zhongwei; Ma, Chunxia; Zhu, Min; Li, Jun; Li, Changting; Gong, Yu; Wang, Leping; Teng, Ling; et al. (Frontiers in Microbiology, 2024)
Lactiplantibacillus plantarum strains are potentially rich sources of probiotics that could help avoid infections. In order to evaluate their efficacy in bolstering resistance to Salmonella typhimurium infection among chicks. In this study, L. plantarum and commercial probiotics were administered via the water supply at a dosage of 1×109 CFU per chicken from days 1 to 7 to establish a protective system for the chicks. On days 8 and 9, S. typhimurium was attacked to investigate the preventive effects and potential mechanisms of L. plantarum in comparison with commercial probiotics. Post-treatment, we took a broad range of measurements, including body weight, immune organ index changes, the viable count of S. typhimurium in the liver, spleen, and cecum, as well as pathological changes in the liver. Our findings demonstrated that both L. plantarum and the commercial probiotic could safeguard chicks from S. typhimurium infection. The data also suggested that probiotic medication could ease weight loss postinfection, lower the bacterial count in the liver, spleen, and cecum, and attenuate liver pathological damage among all treated participants. Subsequently, we did high-throughput sequencing of 16S rRNA to examine the fecal microbiota of the chicks 5  days post-infection. We discovered that both L. plantarum and the commercial probiotic could fend off the invasion of S. typhimurium by affecting the bacterial population of Anaerotruncus, Colidextribacter, and Lactobacillus. Generally speaking, the addition of L. plantarum as a feed additive protects yellow-feathered broilers from S. typhimurium illness, suggesting great potential for commercial uses in the poultry industry.